Anti-wear composition, preparation method and lubricating oil containing anti-wear composition
By introducing specific components and processes into lubricating oil, a stable organic phosphorus-sulfur friction pair interface and nanoparticle filling are formed, which solves the problems of insufficient anti-wear performance and thermal stability of lubricating oil, and achieves high-performance, low-carbon and environmentally friendly lubrication effect.
Patent Information
- Application Number
- CN202510948534.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-10-31
AI Technical Summary
Existing lubricants are insufficient in terms of anti-wear performance, thermal stability and environmental friendliness, making it difficult to meet the high-performance and long-cycle operation requirements of modern industrial equipment. In particular, traditional anti-wear agents are prone to decomposition at high temperatures, produce many corrosive byproducts, and have complex composition and poor process reproducibility.
The method utilizes components such as thiocarboxylic acid esters, polyalkyl phosphate esters, polyether polyesters, graphene-molybdenum oxide composite nanoparticles, azacyclopropane-modified oleylamine, and sulfonated xylenol-formaldehyde resin to form an organic phosphorus-sulfur friction pair interface and nanoparticle micro-filling through a specific process, thereby constructing a stable boundary film layer, enhancing lubrication performance and thermal stability, while avoiding heavy metal contamination.
It significantly improves the anti-wear performance and thermal stability of lubricating oil, reduces the emission of toxic byproducts during equipment operation, conforms to the development direction of green lubricants, and has good industrial adaptability and low-carbon and environmentally friendly characteristics.
Smart Images

Figure CN120865980A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lubricating compositions, specifically relating to an anti-wear composition, a preparation method thereof, and a lubricating oil containing the anti-wear composition. Background Technology
[0002] Lubricating oil plays multiple roles in the operation of mechanical equipment, including reducing friction, minimizing wear, cooling, preventing corrosion, and sealing. It is an important material for ensuring the stable operation of equipment. As industrial equipment develops towards higher loads, higher speeds, and longer lifespans, the performance requirements for lubricating oils are constantly increasing, especially in terms of anti-wear performance, where more stringent requirements are being placed.
[0003] Existing lubricating oil products typically enhance their anti-wear performance by adding anti-wear additives. Among these, traditional anti-wear agents such as phosphate esters, organosulfur compounds, and zinc compounds (e.g., ZDDP) are widely used, forming a protective film on metal-to-metal contact surfaces and reducing wear caused by direct contact. However, these traditional anti-wear agents have some significant drawbacks, such as poor thermal stability at high temperatures, easy decomposition forming corrosive byproducts, environmental friendliness, and even corrosivity to certain metals. Furthermore, some metal-containing additives may adversely affect after-treatment equipment, hindering the development of green and environmentally friendly lubricating oil products.
[0004] In recent years, with increasingly stringent environmental regulations and the demand for improved lubrication system performance, the development of low-carbon, green, low-toxicity, and non-corrosive anti-wear compositions has become a research hotspot. Some studies have attempted to incorporate surfactants, ester compounds, nanomaterials, or multifunctional compound systems into lubricating oils to improve extreme pressure anti-wear performance while maintaining good thermal stability and biodegradability. However, existing technologies still suffer from problems such as complex composition, poor process reproducibility, and poor compatibility with base oils, which restrict their practical industrial application.
[0005] Therefore, there is an urgent need to provide a lubricating oil with good anti-wear properties, strong environmental friendliness, and high thermal stability to meet the needs of modern industrial equipment for high performance and long-cycle operation. Summary of the Invention
[0006] To address the above problems, the present invention aims to provide an anti-wear composition comprising, by weight percentage, the following components:
[0007] Thio fatty acid esters 3-8%; polyalkyl phosphate esters 2-6%; polyether polyesters 4-12%; graphene-molybdenum oxide composite nanoparticles 0.1-2% (mass ratio 1:1); aziridine-modified oleylamine 0.5-3%; sulfonated xylenol-formaldehyde resin 0.3-1.5%; organic complex of titanium / zirconium alkoxide 0.1-1.0%; nonionic surfactant dispersant 1-4%; solvent oil or base oil to 100%; wherein the graphene-molybdenum oxide composite nanoparticles are carboxylated and modified, with an average particle size of less than 50 nm and a solid content of not less than 90%.
[0008] In a preferred embodiment, the thiofatty acid ester is a C12-C18 straight-chain alkyl thioacetic acid ester or a mixture thereof.
[0009] In a preferred embodiment, the polyalkyl phosphate has 3-6 ester groups and the side chain has at least 4 carbon atoms.
[0010] In a preferred embodiment, the molecular weight ratio of the lipophilic group to the hydrophilic group of the polyether polyester is between 3:1 and 5:1, and the terminal hydroxyl group contains not less than 3.0 wt%.
[0011] In a preferred embodiment, the metal element of the organometallic complex is titanium or zirconium, and its ligands are equimolar amounts of n-butanol and isopropanol, with a complexation stability constant K > 10. 4 .
[0012] The present invention also provides a method for preparing an anti-wear composition, comprising the following steps:
[0013] S1. Take graphene and molybdenum oxide in a mass ratio of 1:1, add them to a carboxylating agent solution, stir and react at 50-60℃ for 2-3 hours to generate modified composite nanomaterials, and then dry them by centrifugation for later use.
[0014] S2. Mix polyalkyl phosphate, thiofatty acid ester and polyether polyester at 60-80℃ and stir at a constant speed for 1 hour to obtain base oil phase A.
[0015] S3. Add the modified graphene-molybdenum oxide composite nanoparticles to the solvent oil, add a nonionic surfactant, and sonicate for 20-30 minutes to form a stable suspension B.
[0016] S4. Add the oleylamine modifier, the organometallic complex and the sulfonated resin to the base oil phase A in sequence, heat to 80-90°C, and keep stirring for 30 minutes to form a premixed liquid C.
[0017] S5. Slowly add the suspension B to the premixed liquid C, continue stirring for 1 hour, and then cool to room temperature after vacuum degassing to obtain the anti-wear composition.
[0018] In a preferred embodiment, the frequency of the ultrasonic treatment in step S3 is controlled at 20-25 kHz, the amplitude is controlled at 40-60%, and the treatment time is not less than 25 minutes.
[0019] In a preferred embodiment, the carboxylating agent in step S1 is a 10% aqueous solution of trifluoroacetic acid, and the pH value of the reaction system is controlled between 4.5 and 5.5.
[0020] The present invention also provides a lubricating oil product, the lubricating oil comprising a base oil and the aforementioned anti-wear composition, wherein the anti-wear composition comprises 0.3-5.0% by mass in the lubricating oil.
[0021] In a preferred embodiment, the base oil is a polyalphaolefin synthetic oil with a viscosity index greater than 120, and is mixed with a Group III mineral oil at a mass ratio of 2:1. The physicochemical properties of the lubricating oil include: a kinematic viscosity of 40-60 mm² / s at 40°C, a flash point not lower than 210°C, a pour point not higher than -30°C, a copper strip corrosion grade of less than 1b, and a wear scar diameter of less than 0.45 mm in a four-ball wear test.
[0022] The following explains the "composite construction of organophosphorus-sulfur friction pair interface by thiofatty acid esters and polyalkyl phosphate esters": During the interaction of the friction pair surface, thiofatty acid esters and polyalkyl phosphate esters can undergo adsorption and tribochemical reactions, jointly forming a reaction film with boundary lubrication properties on the metal surface. Specifically, thiofatty acid ester molecules contain polar groups (such as C=S, C–S), which can form strong physical adsorption with the metal surface. Through the orderly arrangement of hydrophobic tails, a dense organic layer is formed, reducing surface energy and helping to reduce direct metal contact (i.e., achieving adsorption and oriented alignment). Under the action of frictional heat and pressure, thiofatty acid esters can undergo tribochemical reactions with the metal surface, generating boundary film structures such as metal sulfides (such as FeS, FeSOx). Simultaneously, the phosphorus-oxygen bonds in the polyalkyl phosphate ester molecules can also react with the metal surface, generating inorganic protective layers such as metal phosphate films (such as FePO4, Fe3(PO4)2), thus achieving the tribochemical reaction film formation. The organophosphorus-sulfur film-forming components have a synergistic effect, and the formed composite reaction film possesses both flexibility and wear resistance. On the one hand, metal sulfides improve the adhesion and sliding properties of the film; on the other hand, metal phosphates enhance the thermal stability and shear strength of the film, thereby significantly improving the wear resistance and extreme pressure bearing capacity of the lubrication interface. When the original film is damaged, the residual thiofatty acid esters and polyalkyl phosphates can be reoriented and reacted at the friction interface to construct a new interfacial film, achieving a certain degree of self-repair of the friction interface.
[0023] Therefore, the construction of this organophosphorus-sulfur friction pair interface can both inhibit direct metal contact on the friction pair surface and continuously provide a chemical protective layer during the friction process, which is one of the core mechanisms for achieving a significant improvement in anti-wear performance.
[0024] Beneficial effects: This invention achieves multi-component synergy in component selection. By combining thiofatty acid esters and polyalkyl phosphate esters, an organophosphorus-sulfur friction pair interface is constructed, which can form a stable boundary film layer on the metal contact surface. At the same time, polyether polyester is introduced as an adhesion-enhancing component to improve the film layer durability and extreme pressure stability of the oil, thereby improving the overall anti-wear performance and shear tolerance of the lubricating medium.
[0025] After carboxylation modification, graphene-molybdenum oxide composite nanoparticles exhibit excellent dispersibility and thermal stability. The nanoparticles can be embedded in the surface of the friction pair to achieve micro-filling and micro-cutting suppression, reducing the wear accumulation rate. The nanostructure particle size is controlled within 50 nanometers, and the solid content is as high as 90%. While ensuring lubrication efficiency, it will not cause deposition and blockage, effectively extending the service life of the lubrication system.
[0026] The azacyclopropane oleylamine, sulfonated xylenol formaldehyde resin and metal alkoxide complex used in this invention work synergistically to enhance oiliness, regulate adhesion and activate the interface. It does not rely on traditional zinc- or chlorine-containing extreme pressure agents, can significantly reduce the emission of toxic byproducts during equipment operation, avoid heavy metal pollution, and is in line with the development direction of green lubricants.
[0027] The raw materials used in the composition of the present invention can all be synthesized and dispersed under normal pressure and temperature conditions, avoiding high-temperature pyrolysis and waste gas generation. Combined with ultrasonic dispersion, low-energy degassing and other processes, the entire preparation process meets the requirements of low carbon and environmental protection and has good industrial adaptability. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the preparation method of the anti-wear composition of the present invention;
[0029] Figure 2 This is a schematic diagram showing the comparative experimental results (wear resistance) of the present invention;
[0030] Figure 3 This is a schematic diagram showing the comparative experimental results (thermal stability) of the present invention;
[0031] Figure 4 This is a schematic diagram showing the comparative experimental results (low-temperature fluidity) of the present invention;
[0032] Figure 5 This is a schematic diagram showing the comparative experimental results (flow performance) of the present invention. Detailed Implementation
[0033] To enhance understanding of the present invention, the present invention will be further described in detail below with reference to embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0034] Example 1 (T1) This embodiment provides an anti-wear composition, the components and their proportions by mass percentage as follows:
[0035] Thio-fatty acid esters (C12-C18 straight-chain alkyl thioacetic acid esters): 3.0%;
[0036] Polyalkyl phosphates (3 ester groups, 4 side chain carbons): 2.0%;
[0037] Polyether-type polyester (lipophilic to hydrophilic group mass ratio of 3:1, terminal hydroxyl content 3.0 wt%): 4.0%;
[0038] Graphene-molybdenum oxide composite nanoparticles (mass ratio 1:1, carboxylated, particle size <50 nm, solid content 90%): 0.1%;
[0039] Azacyclopropane-modified oleylamine: 0.5%;
[0040] Sulfonated xylenol-formaldehyde resin: 0.3%;
[0041] Metal alkoxide complex (metal is titanium, ligands are n-butanol and isopropanol in equimolar amounts, K > 10) 4 ): 0.1%;
[0042] Nonionic surfactant dispersant: 1.0%;
[0043] Solvent oil (high-purity paraffin-based base oil): Top up to 100%.
[0044] Preparation steps (refer to) Figure 1 As shown, the details are as follows:
[0045] S1: Equal masses of graphene and molybdenum oxide were added to a 10% (v / v) aqueous solution of trifluoroacetic acid with a pH adjusted to 4.5-5.5, and the mixture was stirred at 55°C for 2.5 hours. After reaction, the mixture was centrifuged and dried to obtain carboxylated graphene-molybdenum oxide composite nanomaterials.
[0046] S2: Weigh the above polyalkyl phosphate, thiofatty acid ester and polyether polyester, add them to the reaction vessel according to the ratio, maintain the temperature at 65℃, stir at a constant speed for 1 hour to form a uniform and transparent base oil phase A.
[0047] S3: The carboxylated graphene-molybdenum oxide composite nanoparticles obtained in S1 were added to a solvent oil with a volume fraction of 20%, and a non-ionic surfactant was added. The mixture was ultrasonically dispersed for 30 minutes at a frequency of 22 kHz and an amplitude of 50% to obtain nano-suspension B.
[0048] S4: Add aziridine-modified oleylamine, metal alkoxide complex and sulfonated resin sequentially to the base oil phase A, maintain the temperature at 85℃ and continue stirring for 30 minutes to form premixed solution C.
[0049] S5: Slowly add nano suspension B dropwise to premixed solution C, keep stirring at a constant speed for 1 hour, then perform vacuum degassing to remove air bubbles and residual solvent from the system, and cool to room temperature to obtain a light brown, stable and uniform anti-wear composition.
[0050] This anti-wear composition is added to a base lubricating oil at a mass percentage of 2.0% to formulate a lubricating oil product, wherein the base oil is a mixture of polyalphaolefin synthetic oil and Group III mineral oil at a mass ratio of 2:1.
[0051] Example 2 (T2) This embodiment provides an anti-wear composition, the components of which are as follows by mass percentage:
[0052] Thio-fatty acid esters (C12–C18 straight-chain alkyl thioacetic acid esters): 8.0%;
[0053] Polyalkyl phosphates (with 6 ester groups and at least 4 carbon atoms in the side chain): 6.0%;
[0054] Polyether-type polyester (lipophilic to hydrophilic molecular weight ratio of 5:1, terminal hydroxyl content 3.2 wt%): 12.0%;
[0055] Graphene-molybdenum oxide composite nanoparticles (mass ratio 1:1, carboxylated, particle size <50 nm, solid content ≥90%): 2.0%;
[0056] Azacyclopropane-modified oleylamine: 3.0%;
[0057] Sulfonated xylenol-formaldehyde resin: 1.5%;
[0058] Metal alkoxide complex (metal element is zirconium, ligands are n-butanol and isopropanol, molar ratio 1:1, K>10) 4 ): 1.0%;
[0059] Nonionic surfactant dispersant: 4.0%;
[0060] Solvent oil (paraffin-based low-aromatic light base oil): Top up to 100%.
[0061] The preparation steps are as follows: S1: Graphene and molybdenum oxide were added to a 10% trifluoroacetic acid aqueous solution with a pH controlled at 4.8 at a mass ratio of 1:1, and the mixture was stirred at 60°C for 3 hours. After the reaction was completed, the precipitate was collected by high-speed centrifugation and dried under vacuum at 50°C for 12 hours to obtain carboxylated graphene-molybdenum oxide composite nanoparticles.
[0062] S2: Weigh out polyalkyl phosphate, thiofatty acid ester and polyether polyester, add them to the reaction vessel, and stir at 80°C for 1 hour to obtain a homogeneous and transparent base oil phase A.
[0063] S3: The nanoparticles obtained in S1 are slowly added to a certain amount of solvent oil, and a nonionic surfactant is added. The mixture is then ultrasonically treated for 30 minutes at a frequency of 25 kHz and an amplitude of 60% to form a stable suspension B with a uniform particle size distribution.
[0064] S4: Azacyclopropane-modified oleylamine, metal alkoxide complex and sulfonated xylenol formaldehyde resin were added sequentially to the base oil phase A, and stirred at a constant speed at 90°C for 30 minutes to obtain a dark brown premixed liquid C.
[0065] S5: Under stirring, suspension B is added dropwise to premixed liquid C, stirring is continued for 1 hour, and vacuum degassing is performed under reduced pressure. After cooling to room temperature, a highly dispersed and stable anti-wear composition is obtained.
[0066] The anti-wear composition was then added to the lubricating oil at a mass percentage of 5.0%. The resulting lubricating oil product was formulated with a base oil consisting of a polyalphaolefin synthetic oil and a Group III mineral oil at a mass ratio of 2:1.
[0067] Example 3 (T3) This embodiment provides an anti-wear composition, and the specific formulation of each component by mass percentage is as follows:
[0068] Thio-fatty acid esters (C12–C18 straight-chain alkyl thioacetic acid esters): 5.5%;
[0069] Polyalkyl phosphates (4 ester groups, 5 side chain carbons): 4.0%;
[0070] Polyether-type polyester (lipophilic to hydrophilic molecular weight ratio of 4:1, terminal hydroxyl content 3.1 wt%): 8.0%;
[0071] Graphene-molybdenum oxide composite nanoparticles (mass ratio 1:1, carboxylated, particle size <50 nm, solid content ≥90%): 1.0%;
[0072] Azacyclopropane-modified oleylamine: 1.8%;
[0073] Sulfonated xylenol-formaldehyde resin: 0.9%;
[0074] Metal alkoxide complex (titanium complex, ligands are n-butanol and isopropanol in equimolar ratio, K>10) 4 ): 0.6%;
[0075] Nonionic surfactant dispersant: 2.5%;
[0076] Solvent oil (low aromatic base oil): Top up to 100%.
[0077] The preparation steps are as follows: S1: Graphene and molybdenum oxide were added to a 10% trifluoroacetic acid aqueous solution with pH controlled at 5.0 at a mass ratio of 1:1. The mixture was stirred and reacted at a constant temperature of 55°C for 2.5 hours. After centrifugation to separate the precipitate, it was vacuum dried at 45°C to obtain carboxylated graphene-molybdenum oxide composite nanoparticles.
[0078] S2: Weigh out polyalkyl phosphate, thiofatty acid ester and polyether polyester, add them to a stainless steel reactor, and stir at 70°C for 1 hour to form a transparent and homogeneous base oil phase A.
[0079] S3: The nanoparticles obtained in S1 were added together with a nonionic surfactant dispersant to a portion of the solvent oil and ultrasonically dispersed for 25 minutes at a frequency of 22 kHz and an amplitude of 50% to obtain suspension B, which is a stable light gray color.
[0080] S4: Add the aziridine-modified oleylamine, metal alkoxide complex and sulfonated xylenol formaldehyde resin to the base oil phase A in sequence, heat to 85°C and stir continuously for 30 minutes to form premixed liquid C.
[0081] S5: Slowly add suspension B to premixed liquid C, continue stirring for 1 hour, and perform vacuum degassing treatment. Finally, cool to room temperature to obtain a stable and dispersed anti-wear composition.
[0082] The anti-wear composition was added to a base oil at a mass percentage of 3.0%. The base oil was a mixture of polyalphaolefin synthetic oil and Group III mineral oil in a 2:1 ratio to obtain a lubricating oil sample.
[0083] Comparative Example 1 (C1) This comparative example provides an anti-wear composition with a relatively simple structure and no nanocomposite materials introduced. Its component composition is as follows (by mass percentage):
[0084] Thio-fatty acid esters (C12–C18 straight-chain alkyl thioacetic acid esters): 5.5%;
[0085] Polyalkyl phosphates (ester group number 4): 4.0%;
[0086] Polyether-type polyester: 8.0%;
[0087] Azacyclopropane-modified oleylamine: 1.8%;
[0088] Sulfonated xylenol-formaldehyde resin: 0.9%;
[0089] Metal alkoxide complex (titanium complex): 0.6%;
[0090] Nonionic surfactant dispersant: 2.5%;
[0091] Solvent oil: Top up to 100%.
[0092] Differences: This comparative example does not contain graphene-molybdenum oxide composite nanoparticles, that is, it lacks the nano-anti-wear solid lubricant reinforcing material in the examples, nor has it undergone carboxylation dispersion modification, and the formulation does not contain any inorganic particulate components.
[0093] Preparation process:
[0094] Using the same preparation process as in Example 3 (T3), the preparation and addition of the nano suspension were omitted, and other components were operated according to the same S2 to S5 processes to obtain the comparative anti-wear composition.
[0095] The above comparative anti-wear composition was added at a mass percentage of 3.0% to the same base oil as the main solution (a mixture of polyalphaolefin and Group III mineral oil in a 2:1 ratio) to obtain a comparative lubricating oil sample.
[0096] Comparative Example 2 (C2) This comparative example provides an anti-wear composition without the introduction of metal alkoxide complexes, the components of which are as follows by mass percentage:
[0097] Thio-fatty acid esters (C12–C18 straight-chain alkyl thioacetic acid esters): 5.5%;
[0098] Polyalkyl phosphates (ester group number 4, side chain carbon number not less than 4): 4.0%;
[0099] Polyether-type polyester (lipophilic / hydrophilic mass ratio 4:1, containing 3.1 wt% terminal hydroxyl groups): 8.0%;
[0100] Graphene-molybdenum oxide composite nanoparticles (mass ratio 1:1, carboxylated, average particle size <50 nm, solid content ≥90%): 1.0%;
[0101] Azacyclopropane-modified oleylamine: 1.8%;
[0102] Sulfonated xylenol-formaldehyde resin: 0.9%;
[0103] Nonionic surfactant dispersant: 2.5%;
[0104] Solvent oil: Top up to 100%.
[0105] Note of differences: This comparative example does not contain the organic complex of titanium / zirconium alkoxide. This type of component, which serves as a stabilizer and interfacial ionic bridge in the co-construction of the anti-wear film layer in the main embodiment, has been completely removed in this group to verify the performance impact of its absence.
[0106] Preparation process: The steps S1 to S5 in Example 3 (T3) were performed, except that no metal alkoxide complex was added in step S4, and the remaining operating parameters were the same, and the comparative anti-wear composition was finally obtained.
[0107] The prepared anti-wear composition was added to the same base oil (poly-α-olefin and Group III mineral oil were mixed in a 2:1 ratio) at a mass percentage of 3.0% to obtain the lubricating oil product.
[0108] Comparative Example 3 (C3) This comparative example provides a conventional lubricating oil formulated with reference to existing technology, whose components adopt the typical composition of commercially available medium-performance multipurpose lubricating oils, as follows by mass percentage:
[0109] Mineral base oil (Group II hydrocracking oil, viscosity index approximately 105): 94.8%;
[0110] Zinc dialkyl dithiophosphate (ZDDP): 2.0%;
[0111] Diisobutylaniline (antioxidant): 0.7%;
[0112] Sulfur-phosphorus type extreme pressure agent: 1.0%;
[0113] Nonionic surfactants (polyol esters): 1.5%.
[0114] Differences: This formulation does not contain the graphene-molybdenum oxide nanocomposite particles, metal alkoxide complexes, polyether polyesters or aziridine oleylamines proposed in the invention, nor does it contain compounded synergistic sulfonyl resins. It belongs to the existing general anti-wear lubricating oil system, and the main anti-wear agent source is traditional ZDDP and sulfur-phosphorus extreme pressure agents, which have limitations such as pyrolysis residues and corrosive by-products.
[0115] Preparation method: The components are mixed at room temperature under stirring conditions according to the above proportions, and the mixture is kept uniform to obtain the anti-wear lubricating oil sample in the prior art, without involving any nano-dispersion or complexation treatment steps.
[0116] Comparative Example 4 (C4) This comparative example provides an existing environmentally friendly lubricant formulation that emphasizes being zinc-free, sulfur-free, and halogen-free, while maintaining a simple overall anti-wear structure. Its components, by mass percentage, are as follows:
[0117] Synthetic ester base oil (terrestrial polyether ester): 92.5%;
[0118] Triisobutyl phosphate (metal-free environmentally friendly anti-wear additive): 3.5%;
[0119] Polyetheramine type friction-reducing additive: 2.0%;
[0120] Benzotriazole copper inhibitors: 0.5%;
[0121] Antioxidant (liquid phenols): 1.5%.
[0122] Differences: This formulation does not contain traditional zinc additives (ZDDP) and heavy metal components, and lacks key synergistic components proposed in this invention, such as graphene-molybdenum oxide nanocomposite anti-wear material, metal alkoxide complex, polyether polyester, aziridine oleylamine and sulfonated phenolic resin, resulting in a relatively simple lubricating film structure.
[0123] Preparation method: The above components are mechanically stirred at room temperature for 30 minutes in proportion to obtain an environmentally friendly lubricating oil sample, which does not require high-temperature reaction, ultrasonic dispersion or vacuum degassing treatment.
[0124] Comparative experimental design Experimental Objective: This experiment aims to systematically evaluate the differences in anti-wear performance, thermal stability, low-temperature fluidity, and metal corrosion control capabilities of the anti-wear compositions of the present invention (Examples T1, T2, T3) and various existing technical formulations (Comparative Examples C1–C4) in lubricating oil, thereby verifying the technical advantages of the design of the present invention, such as the synergistic structure of nanoparticles, multifunctional organic components, and metal alkoxide complexes.
[0125] The experimental groups are shown in Table 1: Table 1 Comparative Experiment Groups Grouping Sample type Formula characteristics description T1 Example 1 For all key components, the formulation value is taken as the lower limit of the parameter range. T2 Example 2 For all key components, the formulation value is taken as the upper limit of the parameter range. T3 Example 3 For all key components, the formulation value is taken as the midpoint of the parameter range. C1 Comparative Example 1 Lack of graphene-molybdenum oxide composite nanoparticles C2 Comparative Example 2 Lack of metal alkoxide complexes C3 Comparative Example 3 Traditional commercially available formulations contain ZDDP and sulfur-phosphorus extreme pressure agents, but lack synergistic structural design. C4 Comparative Example 4 Environmentally friendly, metal-free lubricant with a simple structure and no core synergistic components.
[0126] All lubricating oil samples were formulated using the same base oil (poly-α-olefin and Group III mineral oil mixed at a mass ratio of 2:1). The amount of anti-wear composition added in Examples T1–T3 was 2.0%, 5.0%, and 3.0%, respectively; the amount added in Comparative Examples C1–C2 was 3.0%, and the amount added in C3–C4 was the commercially available standard content.
[0127] Test items and methods
[0128] 1. Four-ball wear test (wear resistance): Instrument: MMW-1A Four-Ball Friction and Wear Tester;
[0129] Load: 400 N; Rotation speed: 1450 rpm; Temperature: 75℃; Time: 60 min;
[0130] Measurement index: Wear scar diameter (average value, unit mm);
[0131] 2. Flash point test (thermal stability):
[0132] Method: GB / T 3536-2008 (Open Cup Method);
[0133] Instrument: Digital open-cup flash point tester;
[0134] Unit: ℃
[0135] 3. Pour point test (low temperature flowability):
[0136] Method: GB / T 3535-2006;
[0137] Instrument: Standard pour point apparatus;
[0138] Unit: ℃
[0139] 4. Copper sheet corrosion test (corrosion inhibition capability):
[0140] Method: GB / T 5096-2017
[0141] Conditions: 100℃, 3 hours
[0142] Rating: 1a (best) ~ 4c (worst)
[0143] 5. Kinematic viscosity (flow properties):
[0144] Method: GB / T 265-1988;
[0145] Temperature point: 40℃;
[0146] Unit: mm² / s
[0147] The experimental results are shown in Table 2: Table 2 Comparison of experimental results data Grouping Kinematic viscosity at 40℃ (mm² / s) Flash point (°C) Pour point (°C) Copper sheet corrosion rating (100℃, 3h) Four-ball wear test wear scar diameter (mm) T1 50.9 232 -36 1a 0.42 T2 58.4 243 -33 1a 0.38 T3 52.3 237 -34 1a 0.4 C1 52.1 235 -34 1a 0.48 C2 52 236 -34 1a 0.51 C3 49.6 226 -27 1b 0.62 C4 46.9 242 -36 1a 0.51
[0148] Data Analysis The experimental results show that Examples T1, T2, and T3 are superior to Comparative Examples C1 to C4 in all performance indicators, indicating that the anti-wear composition of the present invention has significant technical advantages in the application of lubricating oil.
[0149] like Figure 2As shown, in terms of four-ball wear performance, the wear scar diameters of T1, T2, and T3 are 0.42 mm, 0.38 mm, and 0.40 mm, respectively, all below 0.45 mm, indicating that the formulation of this invention can form a stable anti-wear film under high-load friction conditions. Among them, T2, due to the use of the upper limit ratio, has the highest content of graphene-molybdenum oxide nanoparticles and multifunctional organic additives, resulting in the strongest anti-wear ability and the smallest wear scar (0.38 mm). In contrast, C1 lacks nanomaterials, C2 lacks metal complexes, and C3 and C4 lack multiple synergistic structures, with wear scar diameters increasing to 0.48 mm, 0.51 mm, 0.62 mm, and 0.51 mm, respectively. This reflects the degradation of anti-wear performance caused by the absence or simplification of different key components, especially the C3 group, which shows the most severe wear, confirming that the traditional ZDDP system has insufficient shear stability under extreme pressure friction conditions.
[0150] like Figure 3 As shown, in terms of thermal stability (flash point), the flash points of T1, T2, and T3 are 232℃, 243℃, and 237℃, respectively, which are significantly higher than those of C3 (226℃) and groups C1 and C2 (235℃ and 236℃), indicating that the lubricating oil system of this invention has stronger high-temperature oxidation resistance. Among them, T2 has the highest flash point, further verifying the ability of the high content of phosphate ester and nanoparticles in the upper limit formulation to synergistically inhibit thermal decomposition reaction.
[0151] like Figure 4 As shown, in terms of low-temperature fluidity (pour point), T1, T3, and C4 all exhibit a value of -36℃, T2 is -33℃, C1 and C2 are -34℃, while C3 is the lowest at only -27℃. This indicates that the polyether-type polyester and graphene-molybdenum oxide particles introduced in the formulation of this invention have good low-temperature dispersion stability in the oil system and will not lead to fluidity deterioration, making them suitable for extremely cold working conditions.
[0152] Regarding the corrosion performance of copper sheets, T1 to T3 and C1, C2, and C4 are all grade 1a, with no corrosion observed; while C3 is grade 1b, showing slight discoloration. This indicates that traditional ZDDP and sulfur-phosphorus extreme pressure agents are prone to decomposition under high temperature conditions to form corrosive intermediates, while the metal alkoxide complex and sulfophenolic resin in the system of this invention have good adsorption stability and corrosion inhibition effect on metal surfaces.
[0153] like Figure 5 As shown, regarding kinematic viscosity at 40℃, all samples exhibited viscosity values ranging from 46.9 to 58.4 mm² / s, meeting the requirements for industrial lubricants. T2 showed the highest viscosity, demonstrating the enhancing effect of high-concentration polyester and multifunctional structure on the consistency of the lubrication system, making it suitable for high-load, slow-speed mechanical systems.
[0154] In summary, Example T3, which adopts the optimal formulation, demonstrates a balanced performance in terms of wear resistance, thermal stability, corrosion control, and flowability. Its performance is superior to the comparative formulation, which lacks key synergistic components, and it has good overall adaptability and engineering applicability. Therefore, it is recommended as the main formulation for industrial promotion.
[0155] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-wear composition, characterized in that, The anti-wear composition comprises the following components by weight percentage: Thio fatty acid esters 3-8%; polyalkyl phosphate esters 2-6%; polyether polyesters 4-12%; graphene-molybdenum oxide composite nanoparticles 0.1-2% (mass ratio 1:1); aziridine-modified oleylamine 0.5-3%; sulfonated xylenol-formaldehyde resin 0.3-1.5%; organic complex of titanium / zirconium alkoxide 0.1-1.0%; nonionic surfactant dispersant 1-4%; solvent oil or base oil to 100%; wherein the graphene-molybdenum oxide composite nanoparticles are carboxylated and modified, with an average particle size of less than 50 nm and a solid content of not less than 90%.
2. The anti-wear composition according to claim 1, characterized in that, The thiofatty acid ester is a C12-C18 straight-chain alkyl thioacetic acid ester or a mixture thereof.
3. The anti-wear composition according to claim 1, characterized in that, The polyalkyl phosphate has 3-6 ester groups and the side chain has no less than 4 carbons.
4. The anti-wear composition according to claim 1, characterized in that, The polyether-type polyester has a molecular weight ratio of lipophilic to hydrophilic groups between 3:1 and 5:1, and contains terminal hydroxyl groups of not less than 3.0 wt%.
5. The anti-wear composition according to claim 1, characterized in that, The metal-organic complex has titanium or zirconium as its metal element, and its ligands are equimolar amounts of n-butanol and isopropanol. The complexation stability constant K > 10. 4 .
6. A method for preparing an anti-wear composition, characterized in that, The method includes the following steps: S1. Take graphene and molybdenum oxide in a mass ratio of 1:1, add them to a carboxylating agent solution, stir and react at 50-60℃ for 2-3 hours to generate modified composite nanomaterials, and then dry them by centrifugation for later use. S2. Mix polyalkyl phosphate, thiofatty acid ester and polyether polyester at 60-80℃ and stir at a constant speed for 1 hour to obtain base oil phase A. S3. Add the modified graphene-molybdenum oxide composite nanoparticles to the solvent oil, add a nonionic surfactant, and sonicate for 20-30 minutes to form a stable suspension B. S4. Add the oleylamine modifier, the organometallic complex and the sulfonated resin to the base oil phase A in sequence, heat to 80-90°C, and keep stirring for 30 minutes to form a premixed liquid C. S5. Slowly add the suspension B to the premixed liquid C, continue stirring for 1 hour, and then cool to room temperature after vacuum degassing to obtain the anti-wear composition.
7. The preparation method according to claim 6, characterized in that, In step S3, the frequency of the ultrasonic treatment is controlled at 20-25 kHz, the amplitude is controlled at 40-60%, and the treatment time is not less than 25 minutes.
8. The preparation method according to claim 6, characterized in that, The carboxylating agent mentioned in step S1 is a 10% aqueous solution of trifluoroacetic acid, and the pH value of the reaction system is controlled between 4.5 and 5.
5.
9. A lubricating oil product, characterized in that, The lubricating oil comprises a base oil and an anti-wear composition according to any one of claims 1 to 5, wherein the anti-wear composition comprises 0.3-5.0% by mass in the lubricating oil.
10. The lubricating oil product according to claim 9, characterized in that, The base oil is a polyalphaolefin synthetic oil with a viscosity index greater than 120, and is mixed with Group III mineral oil at a mass ratio of 2:
1. The physical and chemical properties of the lubricating oil include: kinematic viscosity of 40-60 mm² / s at 40℃, flash point not lower than 210℃, pour point not higher than -30℃, copper strip corrosion grade less than 1b, and wear scar diameter less than 0.45 mm in the four-ball wear test.
Citation Information
Patent Citations
Graphene-reinforced titanium-based nanocomposite material and preparation method
CN107557612A
Graphene-containing lubricating protective additive for lubricating oil
CN112961721A
UHMWPE (Ultra High Molecular Weight Polyethylene)-based composite extruded pipe and preparation method thereof
CN116836473A
Antirust lubricant as well as preparation method and application thereof
CN119242369A
Nano graphene-modified lubricant
US20110046027A1